Prooxidant Mechanisms in Iron Overload Cardiomyopathy. (19th November 2013) - Cheng, Ching-Feng; Lian, Wei-Shiung
Abstract : Iron overload cardiomyopathy (IOC), defined as the presence of systolic or diastolic cardiac dysfunction secondary to increased deposition of iron, is emerging as an important cause of heart failure due to the increased incidence of this disorder seen in thalassemic patients and in patients of primary hemochromatosis. At present, although palliative treatment by regular iron chelation was recommended; whereas IOC is still the major cause for mortality in patient with chronic heart failure induced by iron-overloading. Because iron is a prooxidant and the associated mechanism seen in iron-overload heart is still unclear; therefore, we intend to delineate the multiple signaling pathways involved in IOC. These pathways may include organelles such as calcium channels, mitochondria; paracrine effects from both macrophages and fibroblast, and novel mediators such as thromboxane A2 and adiponectin; with increased oxidative stress and inflammation found commonly in these signaling pathways. With further understanding on these complex and inter-related molecular mechanisms, we can propose potential therapeutic strategies to ameliorate the cardiac toxicity induced by iron-overloading.